STANDAR PELAYANAN PUSKESMAS - Didi Suhendar E.01108055 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article titled Service Standard Health Center, which aims to determine the applicable standard of care in the health center if it is in accordance with the regulations governing the public service, especially on the standard service, as the discovery of a phenomenon that is still less than the maximum indicates the service provided to the community. This type of research is a type of descriptive research using qualitative methods approach. The research was conducted at the district health center Tayan Lower Wire Village. The Service Standards are intended service procedures, service time, cost of services, product services, facilities and infrastructure, as well as the competence of personnel service providers. The results of this study are service procedures are still cumbersome, time is still a long service to visitors, the service charge is not clear because it is not informed, products services provided is not maximal, there is still infrastructure is not suitable to be used, and the average officer in the health center is still high school or equivalent education. The author recommends doctors and health care implementers can improve services, especially in terms of discipline for indiscipline doctors and health care services delivered resulting in a long time, and the health center should pay attention to the existing service standards. Keywords: health center service standards, service procedures, service time, cost of services, product services, facilities and infrastructure, personnel competence providers